Assessment of Crop Loss in Okra (Abelmoschus esculentus L.) Due to Damage by the Major Insect Pests - Subba, B.; Chaudhuri, N.; Senapati, S. K. (International Journal of Bio-resource and Stress Management, 2022)
A field experiment on the yield loss assessment in Okra due to insect-pest was carried out at the research farm of Uttar Banga Krishi Viswavidyalaya, Pundibari, Cooch Behar, West Bengal, India during pre-kharif (15th February–14th May), kharif (15th May–14th August) and post-kharif (15th August–14th November) seasons in 2 years, 2015 and 2016. The experiment was laid out in Randomized Block Design and replicated 6 times. The treatments were T1 (protected by chemical insecticide), T2(protected by organic insecticide), T3 (unprotected). The chemical protection significantly suppressed the jassid and % damage by fruit borer in contrast to organic protection and unprotected in all the 3 seasons. However, the‘t’ test analysis revealed non-significant relation between yield of organically and chemically managed plots and significant relation was found between the yield of untreated with organically and chemically managed plots which is directly related with the abundance of insect population. From chemically management 30.52%, 25.16% and 33.26% and from organically managed plots 29.37%, 20.68% and 32.38% gain in yield was recorded in pre-kharif, kharif and post-kharif seasons, respectively. The avoidable losses from chemically protected plots were 23.39%, 20.00% and 24.88% in 3 seasons, respectively. The same from organically managed plots were 22.73%, 16.98% and 24.39% in 3 cropping seasons respectively as mention above. Since, non-significant different in losses of yield lies between chemically and organically protected plots, organic management for pest management may be opted considering all aspects like health, environment and export earnings.